Optimizing Electrical Stimulation for Promoting Satellite Cell Proliferation in Muscle Disuse Atrophy. (January 2016) - Wan, Qing; Yeung, Simon S.; Cheung, Kwok Kuen; Au, Shannon W.; Lam, Wendy W.; Li, Ying Hui; Dai, Zhong Quan; Yeung, Ella W.
ABSTRACT: Objective: The aim of this study was to investigate the optimal electrical stimulation (ES) protocol in attenuating disuse muscle atrophy by influencing satellite cell activity. Design: This study used a pretest-posttest design. Six ES protocols of different duration (3 hrs day −1 or 2 × 3 hrs day −1 ) and frequencies (2, 10, or 20 Hz) were applied on the soleus muscle in mice ( n = 8 in each group) that were hindlimb-suspended for 14 days. Muscle mass, cross-sectional area and fiber-type composition, and peak tetanic force of the muscles were measured. Immunohistochemical staining was used to evaluate satellite cell content, activation, proliferation, and differentiation. Cell apoptosis was detected by TdT-mediated dUTP nick end labeling (TUNEL) assay. Results: ES at 2 Hz for 2 × 3 hrs day −1 achieved the best effect in attenuating the loss of muscle fiber cross-sectional area and force. This stimulation parameter led to a 1.2-fold increase in satellite cell proliferation and was effective in rescuing cells from apoptosis. Besides, satellite cells in the atrophic muscles required different stimulation protocols for different cellular activities such as activation, proliferation, and myogenic differentiation. Conclusions: This study showed that ES at 2 Hz for 2 × 3 hrs day −1 is the optimal protocol for counteracting muscle disuse atrophy.